STRATEGI MANAJEMEN ORGANISASI DALAM MENGURANGI TURNOVER: PERAN FLEKSIBILITAS JAM KERJA DAN BUDAYA INKLUSIF DALAM LANSKAP KETENAGAKERJAAN INDONESIA 2025-2026 - Ihsan Naluri; Nelly Astuti (Penerbit Lafadz Jaya, 2026)
This study aims to formulate organizational management strategies to mitigate the phenomenon of employee turnover in Indonesia during the 2025-2026 transition period. The study focuses on the role of flexible working arrangements and an inclusive culture as instruments for talent retention in the era of technological disruption. Using a descriptive qualitative method with a Systematic Lietarature Review (SLR) approach, this study synthesises secondary data from industry reports, BPS data from August 2025, and the provisions of the Job Creation Law No. 6 of 2023. as conducted using the frameworks of Social Exchange Theory (SET), Self-Determination Theory (SDT), and the Job Demands-Resources (JD-R) model. Findings indicate that although the unemployment rate has fallen to 4.85%, organisations face the challenge of high turnover intentions due to a shift in workers’ priorities towards work-life balance. The integration of AI can boost productivity by up to 90%, but without proper workload management, the risk of mental exhaustion (quiet cracking) increases. The study concludes that long-term retention requires a transformation of leadership towards a coaching style, the provision of measured autonomy, and regulatory compliance to strengthen the company’s reputation as an employer of choice.